Evaluating Heterogeneity of Primary Lung Tumor Using Clinical Routine Magnetic Resonance Imaging and a Tumor Heterogeneity Index - Hu, Nan; Yin, ShaoHan; Li, Qiwen; He, Haoqiang; Zhong, Linchang; Gong, Nan-Jie; Guo, Jinyu; Cai, Peiqiang; Xie, Chuanmiao; Liu, Hui; Qiu, Bo (Frontiers in Oncology, 2021)
Abstract Objective: To improve the assessment of primary tumor heterogeneity in magnetic resonance imaging (MRI) of non-small cell lung cancer (NSCLC), we proposed a method using basic measurements from T1- and T2-weighted MRI. Methods: One hundred and four NSCLC patients with different T stages were studied. Fifty-two patients were analyzed as training group and another 52 as testing group. The ratios of standard deviation (SD)/mean signal value of primary tumor from T1-weighted(T1WI), T1-enhanced(T1C), T2-weighted(T2WI) and T2 fat suppression(T2fs) images were calculated. In the training group, correlation analyses were performed between the ratios and T stages. Then an ordinal regression model was built to generate the Tumor Heterogeneous Index(THI) for evaluating the heterogeneity of tumor. The model was validated in the testing group. Results: There were 11, 32, 40 and 21 patients with T1, T2, T3 and T4 disease, respectively. In the training group, the median SD/mean on T1WI, T1C, T2WI and T2fs sequences was 0.11, 0.19, 0.16 and 0.15 respectively. The SD/mean on T1C(p=0.003), T2WI(p=0.000) and T2fs sequences(p=0.002) correlated significantly with T stages. Patients with more advanced T stage showed higher SD/mean on T2-weighted, T2fs and T1C sequences. The median THI in the training group was 2.15. THI correlated with T stage significantly(p=0.000). In the testing group, THI was also significantly related to T stages(p=0.001). Higher THI had relevance to more advanced T stage. Conclusions: The proposed ratio measurements and THI based on MRI can serve as functional radiomic markers that correlated with T stages for evaluating heterogeneity of lung tumors.